The Debt to GDP Ratio When Not All Savings Is Used for Consumption - Tanaka, Yasuhito (Issues in Social Science, 2024)
One of the most commonly used conditions for examining fiscal stability is the Domar condition. It compares the interest rate with the economic growth rate under balanced budget (excluding interest payments), and if the former is greater than the latter, public finances will become unstable, and the outstanding government debt will continue to grow. In this note we consider a problem of the debt to GDP ratio when not all savings of consumers of a generation is not used for consumption by consumers of the next generation using a simple macroeconomic model without complicated microeconomic foundation. If not all savings of consumers is not used for consumption, demand is insufficient, and we need larger budget deficit to maintain full employment in a growing economy. However, we show that fiscal instability or un-sustainability do not occur even if not all savings is used for consumption, and the interest rate exceeds the growth rate.